1990
DOI: 10.1021/om00116a012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures of alkaline earth-metal metallocenes: electron diffraction and ab initio investigations

Abstract: The thermal average molecular structures of Sr(C5Me5)2 and Ba(C5Me6)2 have been determined by gas electron diffraction. For both compounds the experimental data are consistent with molecular models where the C5Me5 rings are approximately ^-bonded to the metals and with ring centroid-metal-ring centroid angles close to 150°. The metal-carbon bond distances are ra(Sr-C) = 275.0 (8) pm and ra(Ba-C) = 289.8 (10) pm (mean values). The experimental results are compared to calculations on the model compounds Mg(C6H6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 7 publications
3
38
0
Order By: Relevance
“…These energies are also consistent with previous calculations (26,37), where it was found that the location of a bent equilibrium geometry was basis set and method dependent. The use of reasonably sized all-electron basis sets in the calculations given here may be an important factor in obtaining a bent geometry for CaCp,, and indeed the large number of calculations for the group 2 dihalides (52, 53) and previous calculations of metallocenes (34)(35)(36) suggests that these systems are very sensitive to the basis sets and calculational methods chosen.…”
Section: Geometriessupporting
confidence: 91%
See 1 more Smart Citation
“…These energies are also consistent with previous calculations (26,37), where it was found that the location of a bent equilibrium geometry was basis set and method dependent. The use of reasonably sized all-electron basis sets in the calculations given here may be an important factor in obtaining a bent geometry for CaCp,, and indeed the large number of calculations for the group 2 dihalides (52, 53) and previous calculations of metallocenes (34)(35)(36) suggests that these systems are very sensitive to the basis sets and calculational methods chosen.…”
Section: Geometriessupporting
confidence: 91%
“…A closely related set of molecules are the metallocenes of F group 2, for which gas phase electron diffraction experiments have shown that MgCp, (22) and M~c~* , \23, 24) are linear, while cacpt2 (23,24), s~c~* , , and BaCp , (25,26) are all bent. In the solid phase MgCpz (27) is also linear, while CaCp, (28), CaCp*, (29), and BaCp*, (30) For personal use only.…”
mentioning
confidence: 99%
“…A/D and E/H (Table 2), are in the range 0.3°to 6.7°. Together with the perpendicular arrangement of the ortho-Trip groups (A/B, A/C, E/F, E/G ϭ 82.0Ϫ89.5°), an almost parallel orientation of the C(7)ϪC(12) and C (43)ϪC (48) rings to the central S(1)ϪMϪS(2) plane is achieved (B/I, F/I ϭ 6.3Ϫ13.6°). Despite the formal coordination number of eight, the observed europiumϪsulfur and ytterbiumϪsulfur distances are surprisingly short.…”
Section: Scheme 1 Syntheses Of Compounds 1ϫ5mentioning
confidence: 99%
“…In contrast to these recent examples of pentela-substituted alkaline earth metallocenes, the compounds calcocene [4] and decamethylcalcocene, [5] as well as their strontium analogues, [6,7] are well-known. This topic has been reviewed lately by Hanusa.…”
Section: Introductionmentioning
confidence: 99%